NUMERICAL INVESTIGATION OF ELASTIC WAVE EXCITATION AS A POTENTIAL METHOD FOR RESIDUAL OIL RECOVERY - MOHAMMED AL-SHAMI, TAREQ MOHAMMED (2019)
Seismic wave excitation has shown potential in increasing oil recovery. However, the working mechanism of this technique is not clearly understood.